Pembuatan Alat Peraga di SDK La Mennais Untuk Mengembangkan Kemampuan Peserta Didik dalam Berpikir dan Bernumerasi - Lusia Bince Kumanireng; Roberta Uron Hurit (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
The aim of this service is to develop and improve elementary school students' abilities in thinking and numeracy through making teaching aids. The methods used in this mentoring process are Question and Answer, Discussion and Discovery. This activity is carried out in three stages, namely, the preparation stage; implementation stage; documentation and evaluation. The results obtained were that La Mennais SDK students were very enthusiastic in participating in this activity. Students have a high curiosity in making teaching aids, and all of them are actively involved in this activity. The results found were that all students felt happy and interested in making their own teaching aids. Some students felt challenged in making props, namely in terms of not being neat enough when cutting the prepared manila paper, damage to the shapes that had been formed, but this did not reduce the enthusiasm of these students to make props.